2012
DOI: 10.1136/jnnp-2011-300968
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of apraxia and functional predictions from the Birmingham Cognitive Screen

Abstract: As a model based assessment, BCoS offers a quick and valid way to detect apraxia and predict functional recovery. It enables early and informative assessment of most stroke patients for rehabilitation planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 41 publications
4
94
1
1
Order By: Relevance
“…Although previous studies found no significant association between these tasks (Butler, 2002; Bickerton et al, 2012; see also Riddoch et al, 1989), only two studies investigated both of these tasks in respect of our criteria: According to Jarry et al (2013), both of them are equally difficult whereas Randerath et al (2011) found real tool use to be much easier. This gap is most likely due to methodological variations since the latter authors employed a very structured task (i.e., patients were assessed with only two items, they did not have to select tools in real tool use and they were provided with verbal information about the action to be done).…”
Section: Resultsmentioning
confidence: 82%
“…Although previous studies found no significant association between these tasks (Butler, 2002; Bickerton et al, 2012; see also Riddoch et al, 1989), only two studies investigated both of these tasks in respect of our criteria: According to Jarry et al (2013), both of them are equally difficult whereas Randerath et al (2011) found real tool use to be much easier. This gap is most likely due to methodological variations since the latter authors employed a very structured task (i.e., patients were assessed with only two items, they did not have to select tools in real tool use and they were provided with verbal information about the action to be done).…”
Section: Resultsmentioning
confidence: 82%
“…The Birmingham Cognitive Screen, lasting around 1 hour, is not a test for the acute setting but provides a novel cognitive profile across a range of cognitive processes, amongst others also for praxis functions (Bickerton et al, 2012). In individuals with speech or language disorders, the Apraxia Battery for Adults (ABA-2) can be used for the diagnosis of limb apraxia when administered by experienced speech-language pathologists (Dabul, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Following a stroke incident, a significant proportion of patients can suffer from Apraxia or Action Disorganisation Syndrome (AADS) which, among other symptoms [3], are demonstrated by the impairment of cognitive abilities to carry out activities of daily living (ADL). Recent study [4] estimates that 46% of stroke patients initially have a degree of Apraxia with 24% showing persistence of the problems at 9 months follow-up. Apraxia and AADS can have a dramatic impact on patients independence, and may obviously result in the need for continuous support and care provided by caregivers or specialist cares [5] .…”
Section: Introductionmentioning
confidence: 99%